THE RELATIONSHIP PARENTING OF RARENT WITH SPEECH DEVELOPMENT TO CHIDREN 1-3 YEARS OLD (Study In Pos Sun Early Children Education Glanggang District Beji Pasuruan) - Zumrotul Mufidah; Hindyah Ike; Anita Rahmawati (Jurnal Keperawatan, 2015)
Errors parenting parents can also influence the occurrence of speech disorders in children. In fact thereare parents who educate their children in a way or parenting which are not in accordance with the needsof children that resulted in the child being personally difficult to grow, particularly in aspects of speechdevelopment. Research purposes e the relationship between parenting parents with speech developmentof children aged 1-3 Pos early childhood years in the Garden District of Sun Glanggang Beji Pasuruan.Correlational research design (relationships and associations). Population of all the mothers who havechildren aged 1-3 years in early childhood Pos Park Sun Glanggang Beji Pasuruan District of as manyas 22 people. Sampling technique "total sampling". The independent variable was the pattern ofparenting and dependenya language development of children aged 1-3 years. Data processing andanalysis Editing, Coding, Scoring, Tabulating, Spearman rank with SPSS.Based on the analysis using Spearman Rank test at significance level α = 0.05 was found that ρ <α or0.008 <0.05, which means there is a relationship parenting parents preschool children with speechdevelopment in early childhood Pos Park Sun Glanggang District of Beji Pasuruan.Based on the results of research on parenting parents get most of it is democratic, that is 14 respondents(63.6%), speech development in children aged 1-3 years are mostly normal or appropriate that 15children (68.2%).Parenting parents democratic give children the opportunity for creativity and play according to hiswishes and give freedom to interact with the environment with good supervision so that children are ableto interact and mimic words that are heard by him so that normal development of the child's speech.Keywords: Parenting, Development Talk, children aged 1-3